ASSESSMENT OF PATIENT ANXIETY BEFORE DENTAL TREATMENT - Georgeta Zegan; Daniela Anistoroaei; Eduard Radu Cernei; Vasilica Toma; Alina Sodor; Elena Mihaela Carausu (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study was to identify the prevalence of patient anxiety before treatment and to determine patients' perception of the dental treatment risks. Material and methods. The cross-sectional study was conducted in 210 patients (69 males and 141 females) aged 11-70 years in northeastern Romania, who completed Corah's Dental Anxiety Scale, Revised (DAS-R), Modified Dental Anxiety Scale (MDAS) and Dental Concerns Assessment, Revised (DCA-R). Results. The overall scores of DAS-R indicated high anxiety in 4.3% of patients and severe anxiety or phobia in 2.9% of patients. Overall scores of the MDAS questionnaire indicated 5.2% of very anxious patients and 2.3% of highly anxious or phobic patients with dental treatments. DCA-R indicated high anxiety for injection and extraction. We found statistically significant differences between anxiety levels and age ranges as well as patients' environmental areas (p<0.05). Conclusions. Anxiety to dental practice can affect the quality of treatment and is a serious reason to avoid the dentist office.